Etiology of Anemia, Iron Deficiency among Young Children and Strategies to Overcome (International Journal of Physiology, 2020)
Background: Anemia, iron deficiency, worm infestation and Helicobacter pylori infection is highlyprevalent among young children population in India.Objectives: To understand the aetiology of anaemia, iron deficiency, role of worm infestation and presenceof Helicobacter pylori among young children population and to assess the impact of interventionMethod: 484 children of age 5-12 years from rural schools were enrolled for the study. Blood haemoglobinand serum ferritin were measured. H.pylori status was investigated with the 13C- Urea Breath Test. Stoolspecimen was assessed for the presence of parasites. 140 anemic children were selected for the intervention.They were randomly divided into seven groups of 20 children in each and named as group 1 to 7. 1 as control,2 iron supplementation, 3 treated for H. pylori alone, 4 treated for worms, 5 treated for H. pylori infectionalong with iron supplementation, 6 treated for worms along with iron supplementation & 7 supplementedwith iron along with treatment for H. pylori and deworming (for duration and dose refer Methodology inthe text).Results: Of the 484 children, 30.4% were anemic. 18.8% children were iron deficient, of which, 50.3%were anemic. 13.2% children were positive for H.pylori and 50.0% children are infested with potentiallypathogenic parasites. Intervention studies showed that the Group 7 children showed significant rise inhemoglobin and serum ferritin in comparison.Conclusion: Childhood anemia continues to be a significant public health problem in school children andtargeted intervention to iron deficiency either alone or in combination (Iron deficiency, worm infestation andH. pylori infection) can reduce the burden.